Analisis Hubungan Profitabilitas dengan Harga Saham Sektor Usaha Makanan dan Minuman di Bursa Efek Jakarta - Budiman, Ignatius Sarto Kothson (Bina Nusantara University, 2007)
Stock price movement was influenced by many factors, such as company performance, interest level, political factors, security, etc. Article purposes to get approximate probability on the influence between company profitability level and stock price movement that was traded on the Jakarta Stock Exchange, it also considered external factor influence on the stock price movement. The profitability ratio was represented by Net Profit Margin (NPM), Return On Investment (ROI), and Return On Equity (ROE). The research result indicated that the profitability ratio, such as Net Profit Margin (NPM) and Return On Investment (ROI) have significant influence the stock price movement while Return On Equity (ROE) did not have significant influence on the stock price movement.